OPTIMIZATION OF THE EXTENT OF SURGERICAL TREATMENT FOR INVASIVE CERVICAL CANCER - A. L. Chernyshova; L. A. Kolomiets; I. G. Sinilkin; V. I. Chernov; O. V. Pankova; А. Yu. Lyapunov (Сибирский онкологический журнал)
The study included 26 patients with stage Ia1 – Ib1 cervical cancer who underwent organ-preserving surgery (transabdominal trachelectomy). To visualize sentinel lymph nodes, lymphoscintigraphy with injection of radioactive lymphotropic isotope, 99mTc-labelled nanocolloid, was performed the day before surgery. Intraoperative identification of sentinel lymph nodes using gamma probe was carried out to assess which lymph nodes had taken up the radionuclide. Detection of sentinel lymph nodes in cervical cancer patients can accurately predict the pelvic lymph node status, assess the stage of the disease, individualize the extent of surgery and determine indications for organpreserving surgery.